Physical education teachers' (lack of) gymnastics instruction: an exploration of a neglected curriculum requirement. Issue 1 (2nd January 2020) - Robinson, Daniel B.; Randall, Lynn; Andrews, Erin
ABSTRACT: Gymnastics is named as one of four or five broad movement domains within all of Canada's provincial/territorial physical education (PE) curriculums. However, in practice gymnastics is afforded less relative instructional time than are all other movement domains. In light of this observation, we researched Atlantic Canadian PE teachers' gymnastics instruction, aiming to answer three primary research questions: (1) Why does gymnastics occupy such a limited (relative) amount of instructional time?; (2) What value do PE teachers see in teaching gymnastics?; and (3) How can PE teachers develop the requisite competence and confidence to offer more gymnastics instruction in their PE programs? Employing a series of on-line focus group interviews with purposefully selected PE teachers, our results indicated that participants did indeed value gymnastics. Participants also believed the lack of gymnastics instruction was due to PE teachers' strong focus on other areas/topics, as well as their lack of competence and confidence in teaching gymnastics. Herein, we offer a summary discussion of these results as well as suggestions for future practice and inquiry. The results and discussion should be of interest to those who share an interest in PE, curriculum inquiry, and gymnastics instruction, particularly within Western schooling contexts.